PENGEMBANGAN GOOD CORPORATE GOVENANCE DALAM RANGKA REFORMASI BADAN USAHA MILIK NEGARA - Jubaedah1, Edah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
Corporate governance is one concept which is applied in recent years to improve corporate performance, especially state-owned corporations or BUMNs. In order to improve the BUMN?s performance, Indonesian government should reform its government corporations. One way to reform BUMNs is through applying the concept of corporate governance. There are five basic principles in good corporate governance: transparency, accountability, responsibility, liability and independency. The five principles should be implemented by all actors in BUMNs including the government as the owner and the regulator of BUMNs.